Packaging Quality in the FMCG Supply Chain: A Case Study of Leaking Non-Dairy Creamer (NDC) Packages at Company XYZ - Thomas, Vanessa; Mulyono, Nur Budi (Integrasi Sains Media, 2025)
In Indonesia's highly competitive FMCG market, product quality is critical in maintaining customer loyalty and protecting brand reputation. Company XYZ, a key player in this sector, recently encountered significant challenges due to packaging defects, specifically leaks in its Non-Dairy Creamer (NDC) product line. These defects have led to customer dissatisfaction and threaten the company's relationship with a major client. This study aims to identify the root causes of these packaging failures and propose effective solutions to enhance packaging quality. A qualitative research approach involved semi-structured interviews with key stakeholders and analyzing internal communication records. Root Cause Analysis (RCA) tools, such as Causal Factor Charting and the 5 Whys method, were utilized to uncover the underlying issues. The findings revealed two primary causes: the Quality team's lack of expertise in conducting thorough risk assessments for packaging designs and insufficient knowledge in evaluating the structural integrity of modified packaging. To address these issues, the study recommends implementing standardized risk assessment protocols, conducting comprehensive packaging performance tests, and enhancing training programs for quality management personnel. By adopting these measures, Company XYZ can reduce packaging defects, improve customer satisfaction, and strengthen its competitive position in the dynamic FMCG industry.